Clinical characteristics and risk factors for mortality in COVID-19 patients with diabetes: A literature review - Iskandar, Arik (BKM Public Health and Community Medicine, 2021)
Objective: Diabetes is one of the comorbid causes of death for patients with COVID-19. The Indonesian government records diabetes as one of the comorbidities with the highest proportion of causes of death. This study is a literature review study that aims to describe the clinical character and risk factors for death in diabetic patients with COVID-19 disease. Methods: A literature review was conducted by searching for articles from the PubMed and Google Scholar databases. Inclusion criteria were open access, articles in English, and full text published in journals between 2020 to 2021. The keywords used are "coronavirus disease 2019 AND Clinical Characteristics AND Diabetes". Results: the results of the study found 16 articles that matched, namely Covid-19 patients with diabetes. The clinical characteristics of the patients were 57% male. The average age of the patient was 68 years with other comorbid diseases, the highest was hypertension 57%, heart disease 29%, and followed chronic kidney disease 9.8%. The most common signs and symptoms were fever 64%, cough 59%, fatigue 45%, Dyspnea 43%. The highest risk factors, namely age 70 years, comorbid hypertension, and male sex contributed to the death of COVID-19 patients with diabetes. Conclusion: the clinical characters that appear are fever, cough, fatigue, and difficulty breathing. The risk factor for death in COVID-19 patients with diabetes is age 70 years. Hypertension also contributes to mortality. Comprehensive efforts are needed to identify risk factors early and carry out effective treatment in a timely manner to reduce the mortality of COVID-19 patients with diabetes.